2019
DOI: 10.1186/s12944-019-1112-6
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic index of plasma is a novel and strong predictor associated with fatty liver: a cross-sectional study in the Chinese Han population

Abstract: Background Atherogenic index of plasma (AIP) has been reported to be an important predictor for coronary artery disease and obesity. However, few studies has yet systematically evaluated the association between AIP and Fatty Liver (FL) and its advantage in FL prediction compared with BMI, waist, SBP, DBP, BG, ALT and AST. Methods A total of 7838 participants aged from 19 to 93 years were included in this study. Height, weight, waist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 79%
“…AVI is used to assess general volume, and it has been highly associated with dysfunction of glucose metabolism [37]. Researches found that there were concordances between increased AIP and the incidence of FL [17,18]. TyG are often used to explore the relationship between insulin resistance and excessive visceral fat accumulation [38,39].…”
Section: Roc Curves and Auc For Indices In Identifying Flmentioning
confidence: 99%
“…Simultaneously, AIP was independently correlated with CHD in males but not in females [30]. Similarly, Gaojun Cai et al found that in the Han Chinese population, AIP was a predictor for the incidence of CAD [31]. In a study of 315 Chinese patients with suspected or established CAD, the serum FGF19 level was an independent predictor of the Gensini score, which represents the presence and severity of CAD [11].…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, AIP is a useful tool to evaluate the risk of cardiovascular diseases. 35 AIP has been associated with heart failure, obesity and non-alcoholic fatty liver disease, 36 38 all of which belong to important comorbidities of psoriasis. One study on type 1 diabetes mellitus found an association between triglyceride-to-HDL ratio and hs-CRP level, and they hypothesize that elevated abnormal lipid profile would prompt the formation of foam cells in the arterial wall and increase the inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%